2020
DOI: 10.1097/hjh.0000000000002381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of single-pill combination therapy on adherence, blood pressure control, and clinical outcomes: a rapid evidence assessment of recent literature

Abstract: The 2018 European Society of Cardiology/ European Society of Hypertension Guidelines for the management of arterial hypertension raised the need for evidence to support the use of single-pill combination (SPC) therapy in preference to free-dosed therapy for hypertension. This systematic rapid evidence assessment sought to determine if initiating SPC therapy improves adherence, blood pressure (BP) control and/or cardiovascular outcomes vs. initiation of free-dose combination therapy. Methods: Rapid evidence ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 74 publications
2
34
0
2
Order By: Relevance
“…A recent population-based retrospective cohort study found that the risk of primary outcome (composite of death or hospitalization for acute myocardial infarction, heart failure, or stroke) was lower in patients taking single-pill fixed-dose combination treatment in the intention-to-treat analysis only, while if the analysis was limited to patients who remained adherent to medication (on treatment analysis) the significance of the association was lost, stressing the key role of treatment adherence [37]. In a recent review, Tsioufis et al concluded that further evidence is needed to determine if the increase in adherence seen in patients taking single-pill combinations will translate into better BP control and improved CV outcomes [45]. In this context, only three studies have investigated this aspect using ABPM [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…A recent population-based retrospective cohort study found that the risk of primary outcome (composite of death or hospitalization for acute myocardial infarction, heart failure, or stroke) was lower in patients taking single-pill fixed-dose combination treatment in the intention-to-treat analysis only, while if the analysis was limited to patients who remained adherent to medication (on treatment analysis) the significance of the association was lost, stressing the key role of treatment adherence [37]. In a recent review, Tsioufis et al concluded that further evidence is needed to determine if the increase in adherence seen in patients taking single-pill combinations will translate into better BP control and improved CV outcomes [45]. In this context, only three studies have investigated this aspect using ABPM [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Наиболее часто для повышения приверженности применялась оптимизация режима приема лекарств, которая заключалась в назначении ФК вместо приема нескольких лекарственных препаратов [7,8,11,[16][17][18][20][21][22]26]. Показана эффективность данного подхода -увеличение среднего балла по шкале МГ-4, доли приверженных пациентов по шкале МГ-4 и по данным оригинального опросника, повышение комплаентности при подсчете таблеток, что согласуется результатами аналогичных зарубежных исследований [27].…”
Section: Discussionunclassified
“…In this study, the mRNA expression levels of SREBP‐1 and FASN in kidney were obviously increased in nifedipine‐treated group, but down‐regulated in combination group. In addition, clinical and experimental evidence suggested that dyslipidemia is a cause for the progression of the accumulation of lipid in renal cells and chronic kidney disease 16,25 . SNX significantly reduced the nifedipine‐induced dyslipidemia in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ligustilide‐rich total lactones isolated from SNX regulated the lipid metabolic disorder 15 . Combination therapy was recognized to apparently alleviate patient adherence, and some evidence suggested combination therapy can improve the antihypertensive effect and cardiovascular outcomes 16 . The aim of this study was to observe the synergistic antihypertensive effect and to explore whether SNX mitigate nifedipine‐induced renal lipotoxicity.…”
Section: Introductionmentioning
confidence: 99%